2015
DOI: 10.1021/acs.jpcc.5b10694
|View full text |Cite
|
Sign up to set email alerts
|

Operating and Sensing Mechanism of Electrolyte-Gated Transistors with Floating Gates: Building a Platform for Amplified Biodetection

Abstract: Electrolyte-gated transistors (EGTs) with floating gates (FGs) are an emerging platform for label-free electronic biodetection. Advantages of floating gate EGTs (FG-EGTs) include signal amplification and inherent sensitivity to small voltages, on the order of 10 mV, associated with chemical binding events on the floating gate electrode surface. Here we examine how the performance of these devices depends on their architecture, specifically the relative sizes (areas) of the control gate, the floating gate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 54 publications
(136 reference statements)
4
79
0
Order By: Relevance
“…The sensing part extends off chip and can be immersed into the solution without the transducer part. 20 A similar concept was also reported for an organic electrochemical transistor-based sensor system employing a floating gate 31 and was used to detect gluten. 32 Another concept that has no direct contact between the active material and the electrolyte or analyte, is the internal ion-gated transistor (IGT), see Fig.…”
mentioning
confidence: 86%
“…The sensing part extends off chip and can be immersed into the solution without the transducer part. 20 A similar concept was also reported for an organic electrochemical transistor-based sensor system employing a floating gate 31 and was used to detect gluten. 32 Another concept that has no direct contact between the active material and the electrolyte or analyte, is the internal ion-gated transistor (IGT), see Fig.…”
mentioning
confidence: 86%
“…Recently, Frisbie and co-workers systematically investigate a correlation between the potential change of an extended-gate (= a floating-gate) electrode and threshold voltage (V TH ) in TFTs. 28 In that report, they demonstrated that a negative V TH shift in an organic TFT was derived from the surface modification of a gold floating-gate electrode using SAM (= alkanethiol derivatives). In general, the work function of the gold electrode adsorbed with alkanethiol derivatives is shallower than that of the untreated gold electrode.…”
Section: ¹1mentioning
confidence: 99%
“…The system comprises a supply electrode, ultimately controlling the voltage applied to the gate (V GATE ), the sensing pad electrode which behaves like a floating gate (V PAD ) where DNA hybridisation occurs and the FET itself acting as transducer. It is possible to model the voltage dropped at the gate electrode through the addition of the sensing pad via an extended gate arrangement by relating the voltage to both the capacitance of the gate (C GATE ) and the capacitance of the semiconductor channel (C FET ) and their respective areas [29,30]. According to an investigation performed in [29] by S. P White et al, in order to reduce the effective voltage drop, the area of the gate must be at least 150 times greater than the area of the semiconductor.…”
Section: Sensor Setupmentioning
confidence: 99%
“…It is possible to model the voltage dropped at the gate electrode through the addition of the sensing pad via an extended gate arrangement by relating the voltage to both the capacitance of the gate (C GATE ) and the capacitance of the semiconductor channel (C FET ) and their respective areas [29,30]. According to an investigation performed in [29] by S. P White et al, in order to reduce the effective voltage drop, the area of the gate must be at least 150 times greater than the area of the semiconductor. If this ratio is not satisfied, and the area of the gate is lowered compared to the semiconductor area, then transistor turn-on is not as sharp, FET ON current is reduced and there is also a noticeable hysteresis.…”
Section: Sensor Setupmentioning
confidence: 99%